HCV Interplay With Mir34a: Implications in Hepatocellular Carcinoma - Badami, Ester; Carcione, Claudia; Chinnici, Cinzia Maria; Tinnirello, Rosaria; Conaldi, Pier Giulio; Iannolo, Gioacchin (Frontiers in Oncology, 2022)
Since its identification, HCV has been considered one of the main causes of hepatitis and liver cancer. Currently, the molecular mechanisms of HCC development induced by HCV infection have not been sufficiently clarified. The recent discovery of novel treatments that inhibit HCV replication gave rise to new questions concerning HCC mechanisms. In particular, the HCV eradication mediated by new direct acting anti-viral (DAAs) drugs does not exclude the possibility of de novo HCC development; this finding opened more questions on the interplay between liver cells and the virus. Different groups have investigated the pathways leading to cancer recurrence in patients treated with DAAs. For this reason, we tried to gain molecular insights into the changes induced by HCV infection in the target liver cells. In particular, we observed an increase in microRNA34a (miR34a) expression following HCV infection of HCC cell line Huh7.5. In addition, Huh7.5 treated with extracellular vesicles (EVs) from the previously HCV-infected Huh7.5, underwent apoptosis. Since miR34 expression was increased in Huh7.5 EVs, we hypothesized a paracrine mechanism of viral infection mediated by miR34a cargo of EVs. The balance between viral infection and cell transformation may raise some questions on the possible use of antiviral drugs in association with antineoplastic treatment.